الطاقة الشمسية الصديقة للبيئة: دراسة استشرافية - شيشة, نوال (جامعة الوادي - University of Eloued, 2023)
في سنة 2030 تنتهي صلاحية اللوحات الشمسية التي دخلت الخدمة في سنة 2000 ، مما أثار قلق العديد من المنظمات والهيئات الدولية عن مصير أطنان اللوحات التي تكب في مفارغ الرمي، ومن هنا تهدف هذه الدراسة الى التعرف على حجم الزيادة في انتاج الطاقات الشمسية للدول الأكثر استخداما للطاقات المتجددة، و إلى الكشف عن نفايات الألواح الشمسية المستخدمة في انتاج الطاقة الكهروضوئية. توصلت الدراسة إلى أن معالجة نفايات الطاقة الشمسية يحتاج إلى تبني استراتيجية وطنية ودولية، لأن النفايات لا تسبب أضرارا لمن يستخدمها أو ينتجها فقط، وانما تأثر على الدول الفقيرة التي ترمى فيها، فالمعادن الصلبة الموجود في النفايات تستطيع التسرب للمياه الجوفية مما يشكل خطرا على البيئة. In 2030, the validity of the solar panels that entered service in the 2000 raised the concern of many international organizations and bodies about what will happen to the tons of solar panels that are dumped every year. The purpose of this study is to determine how much of an increase there has been in solar energy production in the most popular countries for photovoltaic energy production. It aims also to identify the waste solar panels that have accumulated over the years. Because solar energy waste affects developing nations as much as it does its users and producers, the study found that a national and international approach is necessary for its disposal.
The Environmentally Friendly Solar Energy Prospective Study
مقال
Keywords: الطاقات المتجددة ; الألواح الشمسية ; النفايات; renewable energies, solar panels, waste